Pokémon "Go" but for how long?: a qualitative analysis of motivation to play and sustainability of physical activity behaviour in young adults using mobile augmented reality. Issue 5 (3rd September 2022) - Winand, Mathieu; Ng, Alicia; Byers, Terri
ABSTRACT: Purpose : There is a lack of analysis on players' perceptions of mobile augmented reality (MAR) games and their sustainable effect. This study analyses Pokémon Go players motivation to play and their perceived physical activity behaviour. Method : Semi-structured interviews of 12 young adult participants residing in Singapore, aged 21–32 years, were performed between February and April 2017. Participants were 6 regular active players of Pokémon Go and 6 were ex-players. Findings : Findings revealed players were motivated to play to fulfil their needs for competency and relatedness. While the game seemed to impact players' physical activity behaviour, it was not sustained. In addition, already physically active participants may have reduced their physical intensity level when playing. Implications : The study raises questions with regards to the sustained physical activity impact of MAR games for already active young adults. Sport organisations' managers could use MAR games high attractiveness to secure new membership.